Quality Of Life Of Residents In Urban Neighbourhoods Of Pulau Pinang, Malaysia - Salleh, Abdul Ghani; Badarulzaman, Nurwati (Penerbit Universiti Sains Malaysia, 2012)
Residential neighbourhood satisfaction is an important indicator of housing neighbourhood quality which affects individuals' quality of life. This paper aims to examine social, economic and physical features of urban neighbourhoods that contribute to the overall satisfaction of with the neighbourhood which in turn affects positively the overall feelings toward life. Data for the study come from primary source collected through personal interview of households randomly selected using the systematic sampling procedure from households living in middle income residential neighbourhoods in Pulau Pinang, Malaysia. Data are analysed using descriptive statistics of the mean scores of satisfaction based on a Likert scale. The findings of the study indicate the residents were generally satisfied with the overall quality of life. However, the satisfaction level was low for public transport, political activities and cost of living from physical, social and economic aspects respectively.